PERIODONTAL APPROACH TO GINGIVITIS PATIENT WITH FIXED ORTHODONTICS APPLIANCES (PENDEKATAN PERIODONTAL PADA PASIEN GINGIVITIS DENGAN PERANTI ORTODONTI TETAP) - Frita Ferlita Shafri Djohan (Journal of Health and Dental Sciences, 2022)
Comprehensive care of a patient from multidisciplinary periodontics and orthodontic is found in gingivitis cases with patients that use fixed orthodontics appliances. Periodontal pathogenic bacteria were initiated to dental plaque formation, followed by predisposing factors such as fixed orthodontic appliance, orthodontic movement, and bad oral hygiene. This case report describes a female patient (23 years old) who needs treatment at the anterior mandibular region. Clinical examination explained crowding anterior 32, 31, 41, 42 and applied bracket on each tooth. Pocket depth on the facial side was average 6-5 mm, accompanied by bleeding on probing. Periodontal approach for gingivitis used gingivectomy and gingivoplasty with blade number 15c to eliminate gingival pocket on crowding teeth at anterior mandibular region. Evaluation results in one week and one month after surgery showed healthy gingiva with an average probing depth of 3mm. Gingivectomy is a periodontal approach for gingivitis in patients with fixed orthodontics appliances that could create healthy gingiva and follow excellent oral hygiene instructions. DOI : 10.54052/jhds.v1n3.p289-298